(untitled) (Ozone Therapy Global Journal, 2017)
It was only around the 80s of the XIX century that some physicians from Europe and United States began to investigate and use ozone as a medical product. One of them was the Irish Dr. George Stoker (1854-1920), military with the rank of major. While in South Africa he observed that the Zulus transported the wounded at sea level to the high mountains for a week or two to receive purer air and they did heal. Dr. Stoker deduced that the atmosphere at high altitude contained an unusual proportion of pure air. He began in London to treat his patients with a mixture of oxygen and fresh air and founded the "House of Oxygen". Subsequent to his work with oxygen he began to investigate oxygen/ozone mixtures. He published the results of his research in the United Kingdom medical journal, The Lancet. His last contribution was written in 1918, only two years before passing away.